2020
DOI: 10.1177/0265407520962578
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of adoptees’ and nonadoptees’ experience of parenthood and mediating role of dyadic coping

Abstract: As most adoption studies have focused on adopted children and their vulnerability, with scant research on adult adoptees’ outcomes, the aim of the present study was to compare adult adoptees and nonadoptees on their experiences as parents and to explore more deeply the question of the role among adoptees of the conjugal relationship in the context of parenthood. A total of 268 adoptees matched one to one with 268 nonadoptees responded to several standardized scales (attachment, mental health, resilience, motiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 57 publications
2
5
0
Order By: Relevance
“…The partner’s attachment style seems to play a particularly determining role as well. This result is also in line with the observations of Despax, Bouteyre and Guiller (2020) who showed that among adoptees dyadic coping had a mediating role in predicting parental stress. Even if the results of our compared correlations should be replicated, these results underline the importance of relational variables as a risk or protective factor for this population.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The partner’s attachment style seems to play a particularly determining role as well. This result is also in line with the observations of Despax, Bouteyre and Guiller (2020) who showed that among adoptees dyadic coping had a mediating role in predicting parental stress. Even if the results of our compared correlations should be replicated, these results underline the importance of relational variables as a risk or protective factor for this population.…”
Section: Discussionsupporting
confidence: 91%
“…This result is in line with the meta-analysis carried out by DeLuca Bishop, Claxton and van Dulmen (2019) who concluded that, overall, adoptees were just as committed and well-adjusted in their romantic relationships as non-adoptees. These results are also particularly interesting insofar as they partly refute those obtained by Despax, Bouteyre and Guiller (2020) who observed that adoptees had lower dyadic coping scores than non-adoptees. Different results are obtained on the same measure depending on the perspective considered (that of the adopted partner or that of the non-adopted one).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…also lead nonadopted adults to express similar specific attitudes toward parenthood. These similarities may explain why no differences have been observed at the quantitative level between adoptees and nonadoptees on certain variables related to the experience of parenthood (Despax et al, 2020). Other determinants, however, seemed to be specifically linked to their adoption history, showing that this population deserves particular attention from researchers studying parenthood.…”
Section: Experience and Determinants Of Massive Investment In Parenthoodmentioning
confidence: 98%
“…Studying these two extreme attitudes toward parenthood among adoptees would allow us to gain a better understanding of the potential effects of adoption on adoptees' desire to start a family and to think about the keys to helping adoptees who regard parenthood as a source of distress. While adoptees do not differ from nonadoptees on a number of variables related to parenthood (Despax et al, 2020), it is relevant to focus on individuals whose adoption seems to have a real impact on their parenthood. This study also contributes more broadly to the field of research on the long-term outcomes of people who have experienced adversity in childhood.…”
Section: Objectivesmentioning
confidence: 99%